Relationship between pain, quality of sleep, sleep bruxism and patients’ personality among individuals with reported orofacial pain - Sylwia Orzeszek; Helena Martynowicz; Joanna Smardz; Anna Wojakowska; Wojciech Bombała; Andrej Jenca; Mieszko Więckiewicz (Scientific Reports)
Abstract The study aimed to determine the relationship between personality traits, orofacial pain (OFP), and headache. Eligible patients underwent one-night videopolysomnography and completed a series of validated questionnaires assessing sleep quality (ISS- Insomnia Severity Scale, PSQI- Pittsburgh Sleep Quality Index, ESS- Epworth Sleepiness Scale), pain intensity (McGill Pain questionnaire, GCPS- Graded Chronic Pain Scale, HIT-6- Headache Impact Test-6, MIDAS- Migraine Disability Assessment, TMD pain screener- Temporomandibular Disorder pain screener), psychoemotional state (KPS- Sense of Stress Questionnaire, PHQ-9 – Patient Health Questionnaire-9, BDI- Beck Depression Inventory, BAI- Beck Anxiety Index, PSS-10- Perceived Stress Scale-10, GAD-7- Generalized Anxiety Disorder-7), personality traits (IPIP-BFM-20 -International Personality Item Pool- Big Five Markers- 20). Patients who exhibited nervousness and hypersensitivity reported higher perceived pain and greater negative impacts on work and daily activities (p = 0,000). Furthermore, a statistically significant relationship was found between subjective sleep quality and emotional stability scales (p = 0,001 for PSQI, p = 0,000 for ISI, p = 0,001 for ESS). However, no such relationship was observed for objective sleep quality, as measured by polysomnography (p > 0,05). The correlation between the emotional stability scale and each of the questionnaires used to examine anxiety, depression, and stress was very strong and corresponded to p = 0.000. Clinical Trial: Relationship Between Selected Parameters and Bruxism www.ClinicalTrials.gov, identifier NCT04214561.